The compliance of free folic acid supplements among pregnant women in rural areas of Northwestern China: The role of related knowledge - Yang, Jie; Reheman, Zulihumaer; Liu, Yunjie; Wang, Yuan; Wang, Nan; Ye, Jinbiao; Li, Yangyuan; Nie, Jingchun (Frontiers in Public Health, 2023)
Background High prevalence of neural tube defects remains one of the major threats to newborns in rural China. Folic acid supplementation before and during early pregnancy can effectively reduce the risk of neural tube defects. Despite the efforts of the free folic acid mass distribution, the actual usage of folic acid supplements was still suboptimal among rural pregnant women in China. The objective of this study is to investigate if and how knowledge can influence the picking up and intake of the free folic acid supplements distributed by the government. Methods We collected survey data from 821 pregnant women in rural areas of Shaanxi, China, in March and December of 2021. Face-to-face interviews and questionnaire surveys were conducted with every participant. Univariate and multivariate logistic regression analyses were performed to test the relationship between knowledge and dependent variables. Results Our study found that there were 76.4% of pregnant women would pick up folic acid supplements distributed by the government and only 44.5% of women would use folic acid before current pregnancy. Awareness of folic acid policy both affects the picking up (OR: 6.708, 95% CI: 4.672–9.632) and periconceptional intake (OR: 1.912, 95% CI:1.326–2.758) of folic acid supplements. Knowledge of health and nutrition in pregnancy showed no significant relationship with the picking up and periconceptional intake of folic acid supplements but was positively associated with the intake duration (Coefficient: 9.278, 95% CI: 2.966–15.591). Conclusion Despite the relatively high level of picking up, the actual folic acid usage was not ideal among pregnant women in rural areas of China. Folic acid policy awareness was positively associated with the picking up and intake of folic acid before and during conception. Knowledge of health and nutrition about pregnancy was related to a longer duration of folic acid intake but had no impact on the picking up rate and periconceptional intake of folic acid supplements.